2013
DOI: 10.1094/php-2013-1125-02-rs
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Resistance of Peanut to Puccinia arachidis

Abstract: Peanut rust, caused by Puccinia arachidis Speg, is an important foliar disease of peanut (Arachis hypogaea L.) in tropical countries. The best option for disease management is host resistance. The objectives of this project included characterizing peanut genotypes for resistance to P. arachidis, assessing the genetic variation of newly developed Collaborative Research and Support Program (CRSP) peanut breeding lines, and assessing genetic variability among P. arachidis populations. In field studies conducted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…(II) Rust-resistant resources in cultivated species (A. hypogaea L.; Table 2) [35,[52][53][54][55][56][57][58][59][60][61][62][63][64]. Numerous studies have been dedicated to acquiring peanut germplasm resources that exhibit immunity, high levels of resistance, or resistance to rust under diverse conditions; these include field, laboratory, glasshouse, and greenhouse trials.…”
Section: Resources For Peanut Rust Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…(II) Rust-resistant resources in cultivated species (A. hypogaea L.; Table 2) [35,[52][53][54][55][56][57][58][59][60][61][62][63][64]. Numerous studies have been dedicated to acquiring peanut germplasm resources that exhibit immunity, high levels of resistance, or resistance to rust under diverse conditions; these include field, laboratory, glasshouse, and greenhouse trials.…”
Section: Resources For Peanut Rust Resistancementioning
confidence: 99%
“…Recent studies have reported multiple genotypes that exhibit high levels of resistance to rust, such as SATGR 278-18, ICGV 00064, ICG 11426, ICG 11088, ICG 4389, ICG 6022, and ICG 6993 [54][55][56][57][58]. Additionally, various genotypes have been identified as being resistant to rust, including PI 259747, PI 390593, ICGV 94114, ICGV-SM 86021, ICGV-SM 02536, ICG 02194, ICGV 01276, and ICGV 02286.…”
Section: Resources For Peanut Rust Resistancementioning
confidence: 99%
“…Mehan et al (1994) used a 0.1% Tween solution and Subramanyam et al (1983ab) added ''a few drops of Tween 80'' to sterile water. In earlier experiments of this study (Power et al, 2013) a 0.1% Tween 20 solution was used for the inoculum suspension and few lesions developed in the growth chamber studies at 20 and 31 DAI. Although optimum conditions for peanut rust development were maintained in the experiments, differences between results herein and previous studies may also be due to conditions such as photoperiod and plant age.…”
Section: Genotype Staudpc Amentioning
confidence: 99%
“…The objectives of this study were to determine the level of field resistance to peanut rust and components of resistance of (a) newly developed peanut CRSP breeding lines with Bolivian genetic background, (b) commonly grown peanut cultivars in Georgia, and (c) parents of existing breeding populations. Part of this research has been reported previously (Power et al, 2013), as part of a symposium proceedings paper, in which field studies conducted in 2010 and 2011 were included, as well as growth chamber studies that lasted 31 d. The field experiments in this current study were carried out from 2010 to 2013, and the methods for the growth chamber studies were adjusted so that data from 16 d were included.…”
mentioning
confidence: 99%
“…Ketahanan kacang tanah terhadap penyakit bercak dan karat dipengaruhi oleh gen-gen tahan dan faktor lingkungan. Power et al (2013) menyebutkan belum pernah dilaporkan adanya ketahanan yang lengkap pada kacang tanah, ketahanannya hanya bersifat sebagian dan yang berperan beberapa gen minor saja. Selain itu suhu dan kelembapan berpengaruh terhadap perkembangan penyakit dan patogenisitas.…”
Section: Pendahuluanunclassified